Robotic devices and systems in physiotherapy- A review (Journal of Pharmaceutical Negative Results, 2022)
Robotics is a term which is used for the combination of multiple terms such as engineering, technology, rehab etc. Even, the term artificial intelligence has proved to be useful in taking robotics ahead. Walking ability is linked to a variety of daily duties, whilst immobility can considerably reduce the standard of living of those suffering from locomotory illnesses. Researchers from all over the world are working to enhance or develop medicines and gadgets that may aid those individuals.By assisting therapists in delivering ongoing instruction over a long period of time and gathering data to monitor improvement robotics-assisted rehabilitation technology has the potential to improve the efficacy and availability of therapy.This review research summarizes the effort that has gone into the implementation and evolution of robotic systems for rehabilitation.Home-based rehabilitation devices, which make use of readily available state-of-the-art technology, are offered as a long-term solution to the current situation.In order to effectively enroll in this therapy for research reasons, efforts are made to discover the appropriate form of treatment, the amount and quantity of training technique, and the patient's features. Robotic therapy should be considered as a therapeutic tool that may be utilized to provide a more complex, controlled multimodal stimulation to the patient, as well as to affect the development of neural pathways through movement. In order to effectively enroll in this therapy for research reasons, efforts are made to discover the appropriate treatment, the length and quantity of training technique, and the patient's features.